Model Pembelajaran System Layout Kantor berbasis Virtual Laboratory: Penelitian Research & Development di Pendidikan Ekonomi FKIP UHAMKA - Supriansyah Supriansyah; Purnama Syaepurohman (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Office Layout System is a course at Bachelor Degree Program of Economics Education at Faculty of Teacher Training and Pedagogy, University of Muhammadiyah Prof. DR. HAMKA. The students requested to understand and practice make office layout system manually. The researchers designed computer based virtual laboratory to assisst the student study the course. The research and development method used to test the effectivity of instruction by using virtual laboratory system that created by “Sweet Home 3D” software. The result showed that virtual laboratory instruction compared to two grades, as experiment model and control model at Economics Education study program students, at their third year. There was significant differences between the experiment class and control class, it mean that virtual laboratory based instruction of office layout course was effective. Keywords: office layout system, research and development method, virtual laboratory